Relationship between uric acid and technique failure in patients on continuous ambulatory peritoneal dialysis: a long-term observational cohort study. Issue 4 (7th April 2017) - Hsieh, Yao-Peng; Chang, Chia-Chu; Kor, Chew-Teng; Yang, Yu; Wen, Yao-Ko; Chiu, Ping-Fang; Lin, Chi-Chen
Abstract : Objectives: Uric acid (UA) is the product of purine or nucleotide metabolism via the pathway of xanthine oxidase or xanthine dehydrogenase. Although epidemiological studies assessing the role of UA in cardiovascular disease or mortality have produced inconsistent results, the correlation between UA and technique failure in patients on continuous ambulatory peritoneal dialysis (CAPD) remains to be assessed. Design: A retrospective cohort study. Setting: Patients starting CAPD between 2001 and 2009 in a single centre in Taiwan. Participants: A total of 371 patients on CAPD. Primary outcome measures: All-cause and peritonitis-related technique failure. Results: A cohort of 371 participants (43.9% male) was enrolled in the study with a mean age of 55.7±15.9 years at the start of CAPD. During the study period, technique failure occurred in 41 (34.4%) patients in the hyperuricaemia group compared with 49 (19.4%) in the normouricaemia group (p=0.003). In the multivariate Cox regression models, hyperuricaemia at baseline was significantly associated with both a higher risk of technique failure (HR 1.24; 95% CI 1.09 to 1.42, p=0.001) and peritonitis-related technique failure (HR 1.29; 95% CI 1.07 to 1.57, p=0.008). Conclusions: UA was shown to be associated with all-cause and peritonitis-related technique failure in our study. Patients on CAPD with hyperuricaemia should be closely monitored and strategies of increasing survival on CAPD should be taken.